2019
DOI: 10.2139/ssrn.3310264
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grain Size, Dendritic Structure and Crystallographic Orientation on Fatigue Crack Propagation in IN713C Nickel-Based Superalloy

Abstract: The polycrystalline IN713C produced via investment casting is one of the widely-used nickel-based superalloy in automotive and aerospace industries. This alloy, however, has an apparent inhomogeneous microstructure generated during casting and contains dendritic structure that gives rise to strain localisation during loading. Yet, the effect of dendritic structure, grain size and shape as well as crystallographic orientation, which directly influence fatigue property and deformation micromechanism in the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Obviously, a 150-μm pore can be seen clearly, which usually forms at the junction of grain boundaries and plays a key role in the process of inducing crack nucleation. 38 Particularly, there is no crystallographic facet around the pore, but a small rough area is observed in Figure 5C, which is similar to the phenomenon observed by Cervellon et al 39 They believe that the high local plastic activity in this area is a precursor of macro crack growth. Meanwhile, the rough area of the Ni-based superalloy is highly close to the fine granular area (FGA) in the steel structure.…”
Section: D Observationsupporting
confidence: 81%
“…Obviously, a 150-μm pore can be seen clearly, which usually forms at the junction of grain boundaries and plays a key role in the process of inducing crack nucleation. 38 Particularly, there is no crystallographic facet around the pore, but a small rough area is observed in Figure 5C, which is similar to the phenomenon observed by Cervellon et al 39 They believe that the high local plastic activity in this area is a precursor of macro crack growth. Meanwhile, the rough area of the Ni-based superalloy is highly close to the fine granular area (FGA) in the steel structure.…”
Section: D Observationsupporting
confidence: 81%
“…is was found to pave the way for the initiation of cracks at the time of LCF testing, in Goss and Cube oriented grains. An identical study [86] was performed, but with cast bars made of IN713C, which was tested under both LCF and HCF conditions. e results similar to the ones seen in the previous study were observed in this study for specimens subjected to both LCF and HCF testing conditions.…”
Section: Physical and Mechanical Properties And Behaviour Of Ni-based Superalloysmentioning
confidence: 99%
“…us, many studies have been done to investigate how freckling occurs and how it can be handled. Studies regarding freckling [85][86][87][88][89][90][91][92] showed that freckles were formed as a result of interdendritic microsegregation caused by thermosolutal convection, which in turn is mainly caused by density inversion taking place in the mushy zone. Preferential formation of freckles was seen when the thermal gradient and solidification rate during casting were low.…”
Section: Freckle Defect Inmentioning
confidence: 99%
See 2 more Smart Citations